PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN PASIEN RAWAT JALAN (Studi di UPT. Puskesmas Maduran Lamongan) - Pudyartono Pudyartono; Al Asri Hasanah (PROFIT, 2018)
Influence Quality Service And Satisfaction Facilities Outpatient In UPT.Puskesmas Maduran Lamongan. In the era of globalization, the dynamics of the business world is getting harder and tighter, including in the field of health care in this clinic. The higher the level of education and socio-economic condition of society, the needs and demands of society will look increasingly health increase. To be able to meet the needs and demands, no other efforts that can be done, except for health service delivery are well . Industri health services not only on the issue of healing of an illness, but also to focus on disease prevention measures and improving the quality of public health direction even better. The purpose of research is to determine the quality of services and facilities to the satisfaction of outpatients in health centers Maduran Lamongan. This study uses multiple regression analysis and hypothesis testing (Test T and F) with Likert scale. The population in this study were 993 consumer with a sample size of 100 responden. methods Accidental sampling.simultaneous testing showed variable quality of service and facilities together have a significant effect on satisfaction of outpatients at UPT. Health centers Maduran Lamongan with Fhitung amounted to 49 123. By using partial test shows the variable quality of service (X1) of 5,551 and Facilities (X2) is 2,844 significant effect on patient satisfaction outpatient. And the variable quality of service (X1) which is the dominant influence on patient satisfaction outpatient.